The Role of Private Law Rules in Mitigating Collective Harm between Symbolic and Specific Compensation: A Comparative Analytical Study of ISIS Damages against the Yazidis - Mandeel , Asaad; Gatea, Haider (Journal of Legal Sciences, 2026)
This study places private law at the core of post-conflict justice, treating contract and property as social memory to be restored. From Nineveh—where coercion and registry manipulation marked 2014–2017—we propose an exceptional civil framework that reorders proof and outcomes: a conclusive presumption of duress for transactions made under coercive control, and a period of suspicion that suspends the reliability of entries created then and opens simplified challenges. Where free will is absent, legal effect collapses—and restitution in kind takes precedence over money. Relief moves from paper to an executable restitution program: abatement of interference, handover of the premises with inventories and utilities reconnected within 72 hours, and registry correction with a temporary deal-lock to prevent recycling of harm. Long-running contracts are re-balanced—fair price restored, obligations recalibrated—while an account of profits channels unlawful yields into a neighborhood restoration fund. The toolkit is grounded in Iraqi provisions on specific performance, astreinte-style penalties, and evidentiary weight of official records, reinforced by German/French comparative doctrine and housing-land-property restitution standards. Because the harm is collective, the paper deploys class-style civil tools and technical judicial oversight (GIS, utility records, ecclesiastical ledgers), and proposes a Commission for Real Property Claims – Nineveh (CRPC–Nineveh) issuing fast, enforceable and registrable decisions, powered by a three-track finance (forfeitures, public appropriations, international support). Alongside in-kind restitution, institutionalized symbolic measures (a property memory register, living plaques, an annual trust index) sustain the remedy’s impact. In sum, private law becomes a technology of rebuilding trust: a door reopens, a ledger is corrected, and a neighborhood breathes again.